Comparison of Clinical and Epidemiological Features of Shiga Toxin-Producing Escherichia coli O157 and Non-O157 Infections in British Columbia, 2009 to 2011. Issue 4 (2013) - Wang, Xuetao; Taylor, Marsha; Hoang, Linda; Ekkert, Judi; Nowakowski, Craig; Stone, Jason; Tone, Greg; Trerise, Steven; Paccagnella, Ana; Wong, Titus; Galanis, Eleni
Abstract : INTRODUCTION: Shiga toxin-producing Escherichia coli (STEC) are major foodborne agents that have the potential to cause severe enteric illnesses and large outbreaks worldwide. Several studies found non-O157 infections to be clinically milder than O157 STEC infections. OBJECTIVE: To compare the clinical and epidemiological profiles of O157 and non-O157 STEC human infections in British Columbia (BC). METHODS: All STEC cases reported in BC from 2009 to 2011 by four local health authorities were included in the study. Cases were classified according to STEC serotype based on laboratory information. Information was gathered via case interview forms. Data analysis included the χ 2 test and Mann-Whitney test; P<0.05 was considered to be statistically significant. RESULTS: A total of 260 STEC cases were reported, including 154 (59.2%) O157 cases, 63 (24.2%) non-O157 cases and 43 (16.5%) STEC cases with no serotype identified. Hospitalization rate was higher and duration of hospitalization was significantly longer for O157 cases compared with non-O157 cases, but other clinical features were not significantly different. Patients with non-O157 infections were significantly more likely to have travelled outside Canada, less likely to report food exposure at social gatherings and more likely to consume bagged greens and cheese. DISCUSSION: O157 is the predominant O serotype in BC and appeared to be more clinically severe than non-O157 STEC infections. However, the true incidence and severity of non-O157 remain unknown due to our current inability to detect all non-O157 cases. The present study and the literature suggest the need to identify more predictive virulence factors because serotype does not consistently predict disease severity.